Structural and Functional Characteristics of Two Molecular Variants of the Nitrogen Sensor PII in Maritime Pine - Llebrés, María Teresa; Pascual, María Belén; Valle, Carolina; de la Torre, Fernando N.; Valderrama-Martin, José Miguel; Gómez, Luis; Avila, Concepción; Cánovas, Francisco M. (Frontiers in Plant Science, 2020)
High levels of nitrogen are stored as arginine during the last stages of seed formation in maritime pine (Pinus pinaster Aiton). The protein sensor PII regulates the feedback inhibition of arginine biosynthesis through interaction with the key enzyme N-acetylglutamate kinase (NAGK). In this study, the structural and functional characteristics of PII have been investigated in maritime pine to get insights into the regulation of arginine metabolism. Two different forms of PII have been identified, PpPIIa and PpPIIb, which differ in their amino acid sequence and most likely correspond to splicing variants of a single gene in the pine genome. Two PII variants are also present in other pine species but not in other conifers such as spruces. PpPIIa and PpPIIb are trimeric proteins for which structural modelling predicts similar tridimensional protein core structures. Both are located in the chloroplast, where the PII-target enzyme PpNAGK is also found. PpPIIa, PpPIIb and PpNAGK have been recombinantly produced to investigate the formation of NAGK-PII complexes. The interaction of PpPIIa/PpPIIb and PpNAGK is enhanced by glutamine, which relieves the feedback inhibition of PpNAGK activity by arginine. Expression analysis of PpPII genes revealed that PpIIa transcripts were predominant during embryogenesis and germination. The potential roles of PpPIIa and PpPIIb in the regulation of arginine metabolism of maritime pine are discussed.